New insights into procathepsin D in pathological and physiological conditions - Saraswat-Ohri, Sujata (Medknow Publications & Media Pvt Ltd, 2011)
Procathepsin D is a major glycoprotein that is secreted from numerous types of cancer cells including breast, lung and prostrate carcinomas. It affects multiple stages of tumorigenesis that include proliferation, invasion, metastasis and apoptosis. Previous studies showed that the mitogenic effect of procathepsin D on cancer cells was mediated through its propeptide or activation peptide. Recent studies have also implicated the possible use of procathepsin D/activation peptide as a marker of cancer progression. Considering the broad range of functions of procathepsin D, the present review summarizes the three major potentials of procathepsin D-cancer progression, tumor marker and wound healing.